The Influence of Probiotic Lactobacilli and Flaxseed on the Health of Weaned Piglets and Metabolism of Polyunsaturated Fatty Acids (PUFAs) - Sopková D.; Vlčková R.; Andrejčáková Z.; Hertelyová Z.; Gancarčíková S.; Nemcová R. (Folia Veterinaria, 2016)
This study investigated for 14 days post-weaning, the influence of dietary supplementation of synbiotics in the form of probiotic cheeses containing cultures of L. plantarum and L. fermentum and crushed flaxseed (source of ω-3 polyunsaturated fatty acids — PUFAs and fibre) on 36 commercial piglets originating from an infected herd (Coronavirus and E. coli) during the critical period of weaning. We focused on the health and metabolism of PUFAs in this critical period of a piglet’s life. The dietary supplementation positively affected: the overall health state of weaners, reduced diarrhoea by 29 % by 14 days post-weaning and significantly increased the counts of lactic acid bacteria, bifidobacteria and the production of volatile fatty acids. The PUFA concentrations in the m. biceps femoris of the piglets were analysed by gas chromatography. High levels of ω-3 alpha-linolenic acid (ALA) in flaxseed increased significantly the level of ALA, eicosapentaenic acid (EPA) and docosahexaenic acid (DHA) in the pig muscles on days 7 and 14 post-weaning. The levels of ω-6 linolenic acid (LA) were less affected by the diet, but were increased on day 14 post-weaning, while the conversion products of LA, and arachidonic acid (AA), were decreased on days 7 and 14. The increased level of dietary ALA favoured the activity of Δ-6-desaturase for the conversion of ALA to EPA and DHA, at the expense of AA synthesis from LA. The ability of synbiotics to incorporate high levels of DHA in the pig muscles appear prospective for improving the nutritional properties of pork and reducing the occurrence of civilization diseases in consumers of this product of animal origin.